Vida cotidiana e ambiente na beira-rio de Educandos, Manaus-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2007)
This study approaches the question of the perception and appropriation of space in a small settlement constructed on the banks of the Negro river at the port of the Educandos neighborhood, one of the few places in the city of Manaus where we can still identify, by way of spatial/geographic objects, traces of a riparian life that resists and exposes the contradiction of the project for modernity in Manaus. Our analysis understands the objective aspects portrayed in the landscape as well as, fundamentally, the subjective aspects that orient the people s relationship to the place, those which go beyond appearance and return to man/means interaction, whose space is lived, the practical-sensitive relationship that permeates daily life. For this reading whose objective was to identify social values and connections to place through the life experiences of the residents of this fragment of urban life, in addition to creating an interface with other fields of knowledge the theoreticmethodological contribution of the Geography of Perception, whose analysis of environmental experience is based on sentiments called topophilic and topophobic, was sought. A qualitative approach was used to deal with the perceptions and values; a quantitative approach was used for the register of indicators or observable trends. The analysis of field data collected through forms and semi-structured interviews revealed, in terms of the aspects connected with topophobia, the predominance of feelings of indignation and fear in relation to, respectively, the degradation of the environment and the growth in marginality, a result of drug trafficking in the area. In relation to the topophilic aspects, we identified feelings of attachment to the lived environment, provider of material (subsistence) and social resources as well as those that are symbolic of existence. The environmental issue on which we focus here was an opportune theme for deepening reflection on the possibility of implementing diverse alternatives for democratic participation in the process of urban planning. We point out the importance of involving different levels of intervention in social space and of recognizing people s links to the lived space, seeing that the place embodies personal experiences and aspirations and this reality must be understood from the perspective of those who give it meaning.
Keywords: Percepção; Paisagem; Lugar; Perception; Landscape; Place; CIÊNCIAS AGRÁRIAS